Increased Serum Free Light Chains Precede the Presentation of Immunoglobulin Light Chain Amyloidosis - Weiss, Brendan M. (American Society of Clinical Oncology, 2014)
PURPOSE: Patients with immunoglobulin light chain amyloidosis (AL amyloidosis) generally present with advanced organ dysfunction and have a high risk of early death. We sought to characterize monoclonal immunoglobulin (M-Ig) light chains before clinical presentation of AL amyloidosis. PATIENTS AND METHODS: We obtained prediagnostic sera from 20 cases with AL amyloidosis and 20 healthy controls matched for age, sex, race, and age of serum sample from the Department of Defense Serum Repository. Serum protein electrophoresis with immunofixation and serum free light chain (FLC) analysis were performed on all samples. RESULTS: An M-Ig was detected in 100% of cases and 0% of controls (P < .001). The M-Ig was present in 100%, 80%, and 42% of cases at less than 4 years, 4 to 11 years, and more than 11 years before diagnosis, respectively. The median FLC differential (FLC-diff) was higher in cases compared with controls at all time periods, less than 4 years (174.8 v 0.3 mg/L; P < .001), 4 to 11 years (65.1 v 2.2 mg/L; P < .001), and more than 11 years (4.5 v 0.4 mg/L; P = .03) before diagnosis. The FLC-diff was greater than 23 mg/L in 85% of cases and 0% of controls (P < .001). The FLC-diff level increased more than 10% per year in 84% of cases compared with 16% of controls (P < .001). CONCLUSION: Increase of FLCs, including within the accepted normal range, precedes the development of AL amyloidosis for many years.